Toward a Gender-Sensitive Approach of Psychiatric Rehabilitation in Autism Spectrum Disorder (ASD): A Systematic Review of Women Needs in the Domains of Romantic Relationships and Reproductive Health - Dubreucq, Marine; Dubreucq, Julien (Frontiers in Psychiatry, 2021)
Later age of diagnosis, better expressive behaviors, increased use of camouflage strategies but also increased psychiatric symptoms, more unmet needs, and a general lower quality of life are characteristics often associated with female gender in autism spectrum disorder (ASD). Psychiatric rehabilitation has shown small to moderate effectiveness in improving patients' outcomes in ASD. Few gender differences have been found in the response to psychiatric rehabilitation. This might be related to the predominance of males in research samples, but also to the lack of programs directly addressing women's unmet needs. The objectives of the present paper were: (i) to review the needs for care of autistic women in romantic relationships and reproductive health; (ii) to review the existing psychosocial treatments in these domains; and (iii) to evaluate the strengths and limitations of the current body of evidence to guide future research. A systematic electronic database search (PubMed and PsycINFO), following PRISMA guidelines, was conducted on autistic women's needs for care relating to psychiatric rehabilitation in romantic relationships and reproductive health. Out of 27 articles, 22 reported on romantic relationships and 16 used a quantitative design. Most studies were cross-sectional (n = 21) and conducted in North America or Europe. Eight studies reported on interventions addressing romantic relationships; no published study reported on interventions on reproductive health or parenting. Most interventions did not include gender-sensitive content (i.e., gender variance and gender-related social norms, roles, and expectations). Autistic women and autistic gender-diverse individuals may face unique challenges in the domains of romantic relationships and reproductive health (high levels of stigma, high risk of sexual abuse, increased psychiatric symptoms, and more unmet needs). We discussed the potential implications for improving women's access to psychiatric and psychosocial treatment, for designing gender-sensitive recovery-oriented interventions, and for future research.